2012
DOI: 10.1136/thoraxjnl-2011-200956
|View full text |Cite
|
Sign up to set email alerts
|

Single-step QuantiFERON screening of adult contacts: a prospective cohort study of tuberculosis risk

Abstract: BackgroundThe efffectiveness of tuberculosis (TB) contact screening programmes using interferon γ release assays remains uncertain as prospective contact TB risk is not well characterised. Objectives To quantify 2-year TB risk and evaluate screening performance with single-step QuantiFERON TB Gold-In Tube (QFT) in adult contacts. To compare TB risk between QFT tested subgroups stratified by exposure type (smear positive pulmonary (SP) versus non-smear positive (NSP) TB) and age (younger (16-35 years) versus ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…In a German study, Geis and colleagues 22 reported that five (83%) of six contacts with disease had interferon-γ values higher than 10 IU/mL, and suggested that raising the QFT test threshold could improve the positive predictive value and reduce the number needed to treat. By contrast, Haldar and colleagues 23 did not find an association between QFT conversion interferon-γ value and progression to tuberculosis disease among adult contacts in the UK, and Zellweger and colleagues 19 found minimal variability in risk by interferon-γ value in a cohort of contacts in a large European network. Notably, these studies measured interferon-γ values in primarily adult tuberculosis contacts in low endemicity areas, whereas our study enrolled young children in a high transmission area who were known to be QFT negative and were then followed prospectively for QFT conversion and subsequent disease.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a German study, Geis and colleagues 22 reported that five (83%) of six contacts with disease had interferon-γ values higher than 10 IU/mL, and suggested that raising the QFT test threshold could improve the positive predictive value and reduce the number needed to treat. By contrast, Haldar and colleagues 23 did not find an association between QFT conversion interferon-γ value and progression to tuberculosis disease among adult contacts in the UK, and Zellweger and colleagues 19 found minimal variability in risk by interferon-γ value in a cohort of contacts in a large European network. Notably, these studies measured interferon-γ values in primarily adult tuberculosis contacts in low endemicity areas, whereas our study enrolled young children in a high transmission area who were known to be QFT negative and were then followed prospectively for QFT conversion and subsequent disease.…”
Section: Discussionmentioning
confidence: 91%
“…16 Whether higher interferon-γ values represent more recent M tuberculosis exposure, greater aerosolised inoculum, or sustained infection-or simply reflect heterogeneity in human immune responses to M tuberculosis-is unclear. Importantly, evidence for whether higher QFT conversion interferon-γ values are associated with increased risk of progression to active disease is conflicting, 19,[21][22][23] and current management algorithms do not distinguish between interferon-γ values above the QFT manufacturer's recommended test threshold of 0·35 IU/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of the aforementioned review, five new longitudinal studies have been published (122)(123)(124)(125)(126). Table 3 presents the characteristics of all 20 longitudinal studies.…”
Section: Predictive Value For Progression To Tb Diseasementioning
confidence: 99%
“…However, three out of 19 contacts who developed active TB had IFN-c levels ,1.0 IU?mL -1 . HALDAR et al [12] did not find a difference when comparing the magnitude of IFN-c levels and disease progression.…”
mentioning
confidence: 99%